Prevalence of ESBL-Resistant Genes in Birds in Italy—A Comprehensive Review - Muhammad Tahir Sarfraz Khan; Nicoletta Formenti; Giovanni Tosi; Flavia Guarneri; Federico Scali; Muhammad Kashif Saleemi; Eugenio Monti; Giovanni Loris Alborali (Animals)
Antimicrobial resistance (AMR) is a major global concern in both human and veterinary medicine. Among antimicrobial resistance (AMR) bacteria, Extended-Spectrum Beta-Lactamases (ESBLs) pose a serious health risk because infections can be difficult to treat. These Gram-negative bacteria can be frequently found in poultry and in Italy, where such protein production is established. ESBL-producing Escherichia coli, Salmonella and Klebsiella in chicken and turkey may pose a significant public health risk due to potential transmission between poultry and humans. This review aims to assess the prevalence of ESBL-producing E. coli, Salmonella and Klebsiella phenotypically and genotypically in Italian poultry, identifying the most common genes, detection methods and potential information gaps. An initial pool of 1462 studies found in scientific databases (Web of Sciences, PubMed, etc.) was screened and 29 were identified as eligible for our review. Of these studies, 79.3% investigated both phenotypic and genotypic ESBL expression while <semantics>blaCTX−M</semantics>, <semantics>blaTEM</semantics> and <semantics>blaSHV</semantics> were considered as targeted gene families. Large differences in prevalence were reported (0–100%). The <semantics>blaCTX−M−1</semantics> and <semantics>blaTEM−1</semantics> genes were the most prevalent in Italian territory. ESBL-producing E. coli, Salmonella and Klebsiella were frequently detected in farms and slaughterhouses, posing a potential threat to humans through contact (direct and indirect) with birds through handling, inhalation of infected dust, drinking contaminated water, ingestion of meat and meat products and the environment. Considering the frequent occurrence of ESBL-producing bacteria in Italian poultry, it is advisable to further improve biosecurity and to introduce more systematic surveillance. Additionally, the focus should be on the wild birds as they are ESBL carriers.